The Ebola epidemic in West Africa: Humanitarian aid and public opinion in Iceland - Elín Broddadóttir 1992- (2018)
Public support of development cooperation in high-income countries, including humanitarian assistance, is important if low-income countries are to be given an opportunity to improve the situation of their population. This research examined public attitudes in Iceland toward humanitarian aid, with the aid provided by the Icelandic government in September 2014 to fight the Ebola epidemic in West Africa as a case in point. Specifically, it examines which demographic characteristics were related to negative attitudes towards the assistance, and which reasons the public believed influenced the decision to provide aid. A questionnaire about attitudes towards the Ebola epidemic was administered to a sample of 1500 adults from an internet panel established by the Social Science Research Institute of the University of Iceland, and 920 people answered (61% response rate). Quarter of the participants expressed negative attitudes towards the humanitarian aid the government provided in response to the Ebola epidemic. Those who held negative opinion were more likely to be less educated, lean to the right in political orientation and have lower household income. People with negative attitudes towards foreign aid were less likely to believe ethical reasons influenced the decision to provide humanitarian assistance. Both those who hold positive and negative views towards foreign aid recognized to some extent the influence of self-interests in providing humanitarian assistance. To enforce positive attitudes towards foreign aid it is important that governments ensure that development cooperation and humanitarian aid are based on ethical considerations, in addition to educating the public about poverty and development processes. Til að tryggja aukin fjárframlög til þróunarsamvinnu er mikilvægt að almenningur hafi jákvæð viðhorf til þróunarmála. Þessi rannsókn kannaði viðhorf almennings til neyðaraðstoðar sem Ísland veitti til að berjast gegn Ebólufaraldrinum í Vestur Afríku í september árið 2014, og hvaða þættir almenningur telur ...